2013
DOI: 10.7314/apjcp.2013.14.11.6379
|View full text |Cite
|
Sign up to set email alerts
|

S-benzyl-cysteine-mediated Cell Cycle Arrest and Apoptosis Involving Activation of Mitochondrial-dependent Caspase Cascade through the p53 Pathway in Human Gastric Cancer SGC-7901 Cells

Abstract: S-benzyl-cysteine (SBC) is a structural analog of S-allylcysteine (SAC), which is one of the major watersoluble compounds in aged garlic extract. In this study, anticancer activities and the underlying mechanisms of SBC action were investigated and compared these with those of SAC using human gastric cancer SGC-7901 cells. SBC significantly suppressed the survival rate of SGC-7901 cells in a concentration-and time-dependent manner, and the inhibitory activities of SBC were stronger than those of SAC. Flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Mitochondrial-dependent apoptosis is initiated by recruitment and activation of caspase [ 36 ]. Thus, we further ask whether caspase-3 is activated during GNPs induced apoptosis in GCLC siRNA treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial-dependent apoptosis is initiated by recruitment and activation of caspase [ 36 ]. Thus, we further ask whether caspase-3 is activated during GNPs induced apoptosis in GCLC siRNA treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, Bcl-2 gene product acts as an anti-apoptotic agent by binding and antagonising with executioner molecules, such as Bax and Bak (Youle and Strasser, 2008). The p53 expression leads to increase in p53 protein concentration which ultimately enhances the expression of Bax gene which is probably associated with further activation of pro-caspase genes (Youle and Strasser, 2008;Sun et al, 2013). On the similar lines, Hassan et al (2013) reported that the p53 gene is a negative regulator of Bcl-2 gene and acts as a transcriptional activator of the Bax gene.…”
Section: Discussionmentioning
confidence: 99%
“…[ 44 ] Moreover, another water-soluble allyl sulfide isolated from AGE, S-benzyl-cysteine (SBC), could have a cytotoxic activity on human gastric cancer through different pathways such as inducing cell cycle arrest and apoptosis. [ 45 ] In addition, another study demonstrated that garlic extract and its fractions provided properties against melanoma. Among garlic extract fraction, R100 fraction more effective than others in suppressing melanoma cell line.…”
Section: Resultsmentioning
confidence: 99%